Vous êtes sur la page 1sur 5

Useful derivatives

Function Derivative Example

𝑑𝑦 𝑑𝑦
𝑦 = 𝑥𝑛 = 𝑛𝑥 𝑛−1 𝑦 = 𝑥 4 ⇒ 𝑑𝑥 = 4𝑥 3
𝑑𝑥

𝑑𝑦
𝑦 = 𝑒𝑥 = 𝑒𝑥
𝑑𝑥

𝑑𝑦
𝑥 𝑑𝑦 𝑦 = 3𝑥 ⇒ = 3𝑥 (𝑙𝑛3)
𝑦=𝑎 = 𝑎 𝑥 (𝑙𝑛𝑎) 𝑑𝑥
𝑑𝑥

𝑑𝑦 1
𝑦 = 𝑙𝑛⁡(𝑥) =
𝑑𝑥 𝑥

𝑑𝑦 1 𝑑𝑦 1
𝑦 = 𝑙𝑜𝑔𝑎 (𝑥) = 𝑦 = 𝑙𝑜𝑔3 (𝑥) ⇒ =
𝑑𝑥 𝑥𝑙𝑛⁡(𝑎) 𝑑𝑥 𝑥𝑙𝑛⁡(3)

𝑑𝑦
𝑦 = 𝑠𝑖𝑛⁡(𝑥) = 𝑐𝑜𝑠⁡(𝑥)
𝑑𝑥

𝑦 = 𝑐𝑜𝑠⁡(𝑥) 𝑑𝑦
= −𝑠𝑖𝑛⁡(𝑥)
𝑑𝑥

𝑦 = 𝑡𝑎𝑛⁡(𝑥) 𝑑𝑦
= 𝑠𝑒𝑐 2 (𝑥)
𝑑𝑥

𝑑𝑦
𝑦 = 𝑐𝑜𝑡⁡(𝑥) = −𝑐𝑜𝑠𝑒𝑐 2 (𝑥)
𝑑𝑥

𝑑𝑦
𝑦 = 𝑠𝑒𝑐⁡(𝑥) = 𝑠𝑒𝑐⁡(𝑥)𝑡𝑎𝑛⁡(𝑥)
𝑑𝑥

𝑑𝑦
𝑦 = 𝑐𝑜𝑠𝑒𝑐(𝑥) = −𝑐𝑜𝑠𝑒𝑐(𝑥)𝑐𝑜𝑡⁡(𝑥)
𝑑𝑥

𝑑𝑥 𝑑𝑦 1 1 1
𝑥 = 𝑠𝑖𝑛⁡(𝑦) = 𝑐𝑜 𝑠(𝑦) → = = =
𝑑𝑦 𝑑𝑥 cos(𝑦) √1 − 𝑠𝑖𝑛2 (𝑦) √1 − 𝑥 2

© www.teachitmaths.co.uk 2016 24594 Page 1 of 5


Useful derivatives

Function Derivative Example

Chain rule

𝑑𝑦
𝑦 = 𝑠𝑖𝑛2 (𝑥) = 2𝑐𝑜𝑠⁡(𝑥)𝑠𝑖𝑛(𝑥)
𝑑𝑥

𝑑𝑦
𝑦 = 𝑠𝑖𝑛3 (𝑥) = 3𝑐𝑜𝑠⁡(𝑥)𝑠𝑖𝑛2 (𝑥)
𝑑𝑥

𝑑𝑦
𝑦 = 𝑡𝑎𝑛⁡(𝑥 3 ) = 3𝑥 2 𝑠𝑒𝑐 2 ⁡(𝑥 3 )
𝑑𝑥

𝑑𝑦
𝑦 = 𝑒 (𝑠𝑒𝑐𝑥) = 𝑠𝑒𝑐⁡(𝑥)𝑡𝑎𝑛⁡(𝑥)𝑒 (𝑠𝑒𝑐𝑥)
𝑑𝑥

𝑑𝑦
𝑦 = 𝑙𝑛(𝑠𝑖𝑛2 (𝑥)) = 2𝑐𝑜𝑡⁡(𝑥)
𝑑𝑥

© www.teachitmaths.co.uk 2016 24594 Page 2 of 5


Useful derivatives

𝑑𝑦
𝑦 = 𝑥𝑛 ⇒ = 𝑛𝑥 𝑛−1
𝑑𝑥
𝑑𝑦
𝑦 = 𝑥 4 ⇒ 𝑑𝑥 = 4𝑥 3

𝑑𝑦
𝑦 = 𝑒𝑥 ⇒ = 𝑒𝑥
𝑑𝑥
𝑑𝑦
𝑦 = 𝑎𝑥 ⇒ = 𝑎 𝑥 (𝑙𝑛𝑎)
𝑑𝑥
𝑑𝑦
𝑦 = 3𝑥 ⇒ = 3𝑥 (𝑙𝑛3)
𝑑𝑥
𝑑𝑦 1
𝑦 = ln⁡(𝑥) ⇒ =
𝑑𝑥 𝑥
𝑑𝑦 1
𝑦 = log 𝑎 (𝑥) ⇒ =
𝑑𝑥 𝑥ln⁡(𝑎)

𝑑𝑦 1
𝑦 = log 3 (𝑥) ⇒ =
𝑑𝑥 𝑥ln⁡(3)

𝑑𝑦
𝑦 = sin⁡(𝑥) ⇒ = cos⁡(𝑥)
𝑑𝑥
𝑑𝑦
𝑦 = cos⁡(𝑥) ⇒ = −sin⁡(𝑥)
𝑑𝑥
𝑑𝑦 1
𝑦 = tan(𝑥) ⇒ = 𝑠𝑒𝑐 2 (𝑥), where sec(𝑥) =
𝑑𝑥 cos⁡(𝑥)

𝑑𝑦 1 1
𝑦 = cot(𝑥) ⇒ = −𝑐𝑜𝑠𝑒𝑐 2 (𝑥), where cosec(𝑥) = ,⁡co𝑡(𝑥) =
𝑑𝑥 sin(𝑥) tan⁡(𝑥)

𝑑𝑦
𝑦 = sec⁡(𝑥) ⇒ = sec⁡(𝑥)tan⁡(𝑥)
𝑑𝑥
𝑑𝑦
𝑦 = 𝑐𝑜𝑠𝑒𝑐(𝑥) ⇒ = −𝑐𝑜𝑠𝑒𝑐(𝑥)cot⁡(𝑥)
𝑑𝑥

If x is the subject of the formula

𝑑𝑥 𝑑𝑦 1 1 1
𝑥 = sin(𝑦) ⇒ = cos(𝑦) → = = =
𝑑𝑦 𝑑𝑥 cos(𝑦) √1 − 𝑠𝑖𝑛2 (𝑦) √1 − 𝑥 2

[𝑠𝑖𝑛2 (𝑦) + 𝑐𝑜𝑠 2 (𝑦) = 1,⁡⁡Pythagoras' theorem]

© www.teachitmaths.co.uk 2016 24594 Page 3 of 5


Useful derivatives

Extensions
𝑑𝑦
𝑦 = (𝑥 4 + 3𝑥 2 − sin⁡(𝑥))5 ⇒ = 5(4𝑥 3 +6𝑥 2 − cos⁡(𝑥))(𝑥 4 + 3𝑥 2 − sin⁡(𝑥))4
𝑑𝑥
𝑑𝑦
𝑦 = 𝑠𝑖𝑛3 (𝑥) ⇒ 𝑦 = (sin(𝑥))3 ⇒ = 3cos⁡(𝑥)𝑠𝑖𝑛2 (𝑥)
𝑑𝑥
The product:
(the index)(the bracket differentiated) (the bracket reduced by a power of 1)

𝑑𝑦
𝑦 = tan⁡(𝑥 3 ) ⇒ = 3𝑥 2 𝑠𝑒𝑐 2 ⁡(𝑥 3 )
𝑑𝑥
The product:
(the angle differentiated)(the trig function differentiated)(the original angle)

𝑑𝑦
𝑦 = 𝑒 (𝑠𝑒𝑐𝑥) ⇒ = sec⁡(𝑥)tan⁡(𝑥)𝑒 (𝑠𝑒𝑐𝑥)
𝑑𝑥
The product:
(the index differentiated)(the original function)

𝑑𝑦 2𝑥 − sin⁡(𝑥)
𝑦 = ln(𝑥 2 + cos⁡(𝑥)) ⇒ = 2
𝑑𝑥 (𝑥 + cos⁡(𝑥))
𝑑𝑦 2cos⁡(𝑥)sin⁡(𝑥) 2 cos(𝑥)
𝑦 = ln(𝑠𝑖𝑛2 (𝑥)) ⇒ = = = 2cot⁡(𝑥)
𝑑𝑥 𝑠𝑖𝑛2 (𝑥) sin(𝑥)
bracket differentiated
The quotient: bracket

Implicit differentiation
𝑥 3 + 𝑦 2 + sin(4𝑥) − cos(2𝑦) = 8
𝑑𝑦 𝑑𝑦
3𝑥 2 + 2𝑦 + 4 cos(4𝑥) + 2 sin(2𝑦) =0
𝑑𝑥 𝑑𝑥
Differentiate with respect to x, term by term

Parametric differentiation
𝑥 = tan(3𝑡) , 𝑦 = 𝑒 (4𝑡)
𝑑𝑥 𝑑𝑦
= 3𝑠𝑒𝑐 2 (3𝑡),⁡⁡⁡ 𝑑𝑡 = 4𝑒 (4𝑡)
𝑑𝑡

𝑑𝑦 𝑑𝑦 𝑑𝑥 4𝑒 (4𝑡)
= ÷ 𝑑𝑡 = 4𝑒 (4𝑡) ÷ 3𝑠𝑒𝑐 2 (3𝑡) = 3𝑠𝑒𝑐 2 (3𝑡)
𝑑𝑥 𝑑𝑡

𝑑𝑦 𝑑𝑦 𝑑𝑡
Making use of the chain rule, = × 𝑑𝑥
𝑑𝑥 𝑑𝑡

© www.teachitmaths.co.uk 2016 24594 Page 4 of 5


Useful derivatives

The product rule

𝑦 = 𝑓(𝑥)𝑔(𝑥)

𝑑𝑦
= 𝑓(𝑥)𝑔′ (𝑥) + 𝑔(𝑥)𝑓′(𝑥)
𝑑𝑥

𝑦 = 𝑒 (2𝑥) sin⁡(3𝑥)

𝑑𝑦
= 𝑒 (2𝑥) (3cos⁡(3𝑥)) + sin⁡(3𝑥)(2𝑒 (2𝑥) ) = 𝑒 (2𝑥) (3cos⁡(3𝑥) + 2sin⁡(3𝑥))
𝑑𝑥

The quotient rule

𝑓(𝑥)
𝑦=
𝑔(𝑥)

𝑑𝑦 𝑓 ′ (𝑥)𝑔(𝑥) − 𝑓(𝑥)𝑔′(𝑥)
=
𝑑𝑥 (𝑔(𝑥))2

𝑥3
𝑦=
tan⁡(𝑥)

𝑑𝑦 3𝑥 2 tan⁡(𝑥) − 𝑥 3 𝑠𝑒𝑐 2 (𝑥)


=
𝑑𝑥 𝑡𝑎𝑛2 (𝑥)

© www.teachitmaths.co.uk 2016 24594 Page 5 of 5